Sex influence on muscle synergies in a ballistic force-velocity test during the delayed recovery phase after a graded endurance run. Issue 6 (June 2022) - Macchi, Robin; Santuz, Alessandro; Hays, Arnaud; Vercruyssen, Fabrice; Arampatzis, Adamantios; Bar-Hen, Avner; Nicol, Caroline
Abstract: The acute and delayed phases of the functional recovery pattern after running exercise have been studied mainly in men. However, it seems that women are less fatigable and/or recover faster than men, at least when tested in isometric condition. After a 20 km graded running race, the influence of sex on the delayed phase of recovery at 2–4 days was studied using a horizontal ballistic force-velocity test. Nine female and height male recreational runners performed maximal concentric push-offs at four load levels a week before the race (PRE), 2 and 4 days (D2 and D4) later. Ground reaction forces and surface electromyographic (EMG) activity from 8 major lower limb muscles were recorded. For each session, the mechanical force-velocity-power profile (i.e. theoretical maximal values of force ( F ¯ 0), velocity ( V ¯ 0), and power ( P ¯ max)) was computed. Mean EMG activity of each recorded muscle and muscle synergies (three for both men and women) were extracted. Independently of the testing sessions, men and women differed regarding the solicitation of the bi-articular thigh muscles (medial hamstring muscles and rectus femoris). At mid-push-off, female made use of more evenly distributed lower limb muscle activities than men. No fatigue effect was found for both sexes when looking at the mean ground reaction forces. However, the force-velocity profile varied by sex throughout the recovery: only men showed a decrease of both V ¯ 0 (p < 0.05) and P ¯ max (p < 0.01) at D2 compared to PRE. Vastus medialis activity was reduced for both men and women up to D4, but only male synergies were impacted at D2: the center of activity of the first and second synergies was reached later. This study suggests that women could recover earlier in a dynamic multi-joint task and that sex-specific organization of muscle synergies may have contributed to their different recovery times after such a race. Highlights: The use of bi-articular thigh muscles differed between men and women. Muscle synergies were sex dependent. Only men showed decreased theoretical maximal velocity and power 2 days after running. Centers of activity of muscle synergies were shifted later for men 2 days after the race. Sex-specific organization of muscle synergies may explain the different recovery times. Abstract : Fatigue, women, endurance running, EMG, explosive movement, jump, non-negative matrix factorization.